Effectiveness of the fi neness of two South African Portland cements for controllingearly-age temperaturedevelopment in concrete - Graham, P.C.; Ballim, Y.; Kazirukanyo, J. (My University, 2011)
In developing an assessment of the quantum and rate of heat evolution from hydrating cement, an important controllable variable is the fineness of grinding of the cement. This paper presents the results of a project in which two cement clinkers were used to produce cements with five different levels of fineness. These ten cements were then used to make concretes which were subjected to testing in an adiabatic calorimeter to determine the heat evolution characteristics. The results indicate that the effect of increasing fineness on the total amount of heat released during hydration is dependent on the mineralogy and crystal composition of the cement clinker. Also, the potential benefits of a so-called low heat cement can be lost if the cement is too finely ground. Based on simulations of temperature development using the different cement types tested, the results indicate that the fineness of grinding of cement is a more important parameter in the case of concrete elements with high cement contents but of moderate dimensions. In sections of larger dimension, coarse ground cements show lower levels of temperature development with lower thermal gradients.
It is generally agreed that, for a given Portland cement, the rate and amount of heat liberated during the early stages of hydration (up to 28 days) is strongly influenced by the fineness of grinding of the cement (see review by Hooton et al 2005). This is intuitively correct since finer grinding means that the hydration reac¬tions between cement and water will proceed more vigorously at early ages and hence pro¬duce more heat and at a higher maximum rate. However, as Hooton et al (2005) show, opin¬ions vary in the literature as to the sensitivity of the relationship between cement fineness and early-age heat of hydration. Furthermore, when considering different cement types, the significance of the fineness of the cement has to be judged in relation to mineralogical parameters, such as the C3A, C3S and gypsum content, equally important factors in deter¬mining the heat characteristics of cement.